Why woody plant modularity through time and space must be integrated in fire research? - Chiminazzo, Marco Antonio [UNESP]; Charles-Dominique, Tristan; Rossatto, Davi Rodrigo [UNESP]; Bombo, Aline Bertolosi [UNESP]; Fidelis, Alessandra [UNESP] (Oxford Univ Press, 2023)
The response of woody plants to fire is influenced by the timing and spatial distribution of their growth modules relative to the flames. Predictions suggest changes in fire regimes for different vegetation types, emphasizing the need to understand which plant species will thrive and the underlying mechanisms enabling their survival. Considering the modularity of plants over time and space is essential. As plants develop through growth modules' production, their modules can gain increased protection against flames. Additionally, new modules produced farther from the direct impact of the flames may survive by being exposed only to the flame plume. Importantly, the survival capacity of modules during a fire is strongly dependent on trait expression (such as bark production and bud protection) and heat transference from one module to another. Different ecosystems evolved and are maintained by fire, with their vegetation hosting species with a wide diversity of persistence strategies allowing them to insulate their body and resprout new branches after fire disturbance. Changes in fire regime are predicted due to climate change, either by promoting more frequent and/or severe fires or by reducing the number of fire events due to the limitation of fuel load. Predicting the future of fire-driven ecosystems is a complex task as species' survival depends on many factors that vary in space and time. Since plants are constantly experiencing new environments as they grow through meristem development, woody plant modularity, modules morpho-physiological aspects and their integration should be considered when investigating species strategies in fire-prone ecosystems: according to their position and their tissue composition, plants' modules experience fire differently and will contribute differently to other modules and the whole plant survival, with consequences cascading over the overall vegetation structure. Growth modules may hold the key to understanding how fast plants can get protected from fire, ultimately helping us to predict which species will persist across changing fire regimes. We present an empirical example showing how different fire-return intervals translate into distinct pressures on the timing, protection and location of modules, and discuss how these can translate into modifications in the vegetation structure due to climate change.
Keywords: Climate change; fire; grassy biomes; growth form; Miconia albicans; plant architecture; resprouting; savanna; shrub; tree